Military uses of space, 1946 [i.e. 1945]-1991 - Richelson, Jeffrey (Chadwyck-Healey, 1991)
"Provides a detailed record of U.S. military space organizations, operations, and policy from 1945 to the present. . . . Included are a wide variety of document types: memoranda, messages, presidential decision documents, program management directives, histories, organizational manuals, reports and studies. The documents emanate from a wide variety of sources--past and present organizations involved in space systems acquisitions and operations (e.g., the Air Force Space Command, the Air Force Systems Command Space Systems Division), the National Security Council, the Congress and government contractors."